LOVITA LAILLY RAHMASARI. THE APPLICATION OF PAIR CHECK COOPERATIVE LEARNING MODEL WITH CONCRETE MEDIA IN IMPROVING MATHEMATICS LEARNING ABOUT FRACTION FOR THE FOURTH GRADE STUDENTS OF SD NEGERI 1 JLEGIWINANGUN IN THE ACADEMIC YEAR OF 2015/2016.THESIS, TEA - Rahmasari, Lovita Lailly (KALAM CENDEKIA PGSD KEBUMEN, 2016)
The objectives of this research are: (1) to describe the steps on the application of Pair Check Cooperative Learning Model with concrete media, (2) to improve Mathematics learning about fraction through the application of Pair Check Cooperative Learning Model with concrete media, and (3) to find problems and solutions on the application of Pair Check Cooperative Learning Model with concrete mediain improvingMathematics learning about fraction for the fourth grade students of SD Negeri 1 Jlegiwinangunin the academic year of 2015/2016.This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. Subjects of the research were 19 students. Sources of data were derived from students, teacher, and observer. Techniques of collecting data were learning outcomes test, observation, interview, and documentation. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. Data were analyzed using quantitative and qualitative descriptiveanalysis.The results of this research show that: (1) the steps of Pair Check Cooperative Learning Model with concrete media was conducted appropriately through steps as follows: (a) explanation of concept with concrete media, (b) group division, (c) distribution of exercises and concrete media, (d) practice dosing exercises with concrete media, (e) trainer check the answer with concrete media, (f) give coupon to answer correctly, (g) trainer and partner change the role, (h) trainer and partner back to previous team, (i) give rewards; (2) the application of Pair Check Cooperative Learning Model with concrete media can improve Mathematics learning about fraction for the fourth grade students of SD Negeri 1 Jlegiwinangun in the academic year of 2015/2016. It was proven by the increase of learning outcomes in the first cycle 73,68%, in the second cycle 86,40%, and in the third cycle 92,10%; and (3) the problems encountered in the learning, namely: (a) the teacher pays less attention students who face difficulties, (b) the teacher does not guide students in doing assignments. Solutions for these problems are: the teacher pays more attention students who face difficulties, (b) the teacher guides students well in doing assignments.The conclusion of this research is the application of Pair Check Cooperative Learning Model with concrete media can improve Mathematics learning about fraction for the fourth grade students of SD Negeri 1 Jlegiwinangunin the academic year of 2015/2016.